UV radiation promotes anthocyanins biosynthesis in the fruit peel of blood oranges (Citrus sinensis) - Yang, Haijian; Chen, Hao; Wang, Wu; Li, Shuang; Wang, Min; Hong, Lin; Yang, Lei; Hu, Wei (Frontiers in Plant Science, 2025)
IntroductionThe commercial value of blood oranges (Citrus sinensis) is closely linked to the intensity of red pigmentation in the peel and flesh, driven by the accumulation of anthocyanins. While light is a crucial environmental factor for anthocyanin synthesis, the specific effects of different light spectra, particularly ultraviolet (UV) radiation, on peel pigmentation have not been fully elucidated.MethodsIn this study, the effects of light spectra on anthocyanin biosynthesis in blood orange peel were systematically studied through three treatments of visible light (VL), UV and complete shading (CK). These treatments were combined with transcriptome, anthocyanin targeted metabolome and weighted gene coexpression network analysis (WGCNA).Results and DiscussionAfter 40 days, UV-treated fruit exhibited significantly higher anthocyanin content and color index (CI) than other treatments, with a significantly positive correlation between the two. Metabolomics identified four key anthocyanins, including cyanidin-3-o-glucoside and its 2 derivatives, as the primary contributors to pericarp coloration, with their levels significantly increased under UV exposure. WGCNA screened three core gene modules closely associated with anthocyanin metabolism, and further identified three glycosyltransferase genes (ugt79b1, bz1 and GT1) as hub genes involved in anthocyanin accumulation. This study demonstrates that UV light enhanced anthocyanin synthesis in blood orange peel by activating downstream glycosylation pathways, providing both a theoretical basis and technical approach for improving commercially market value of blood orange through light regulation.